CXCL10 levels identify individuals with rapid fibrosis at 12 months post‐transplant for hepatitis C virus and predict treatment response. (21st April 2014) - Joshi, Deepak; Carey, Ivana; Foxton, Matthew; Al‐Freah, Mohammed; Bruce, Matthew; Heaton, Nigel; Quaglia, Alberto; O'Grady, John; Aluvihare, Varuna; Agarwal, Kosh
Abstract Backgrounds Recurrent hepatitis C virus (HCV) infection is universal post‐transplantation. Fibrosis (F) stage ≥2 at 12 months identifies patients with rapid fibrosis progression. Antiviral therapy (AVT) remains the only option to attenuate fibrosis progression. We hypothesized that CXCL10 levels can distinguish between slow and fast fibrosis progression at 12 months, development of F ≥ 4 post‐transplantation, and help predict treatment response in patients undergoing AVT. Methods All patients that had undergone primary liver transplantation at King's College Hospital, London, between 2000 and 2011 were identified. Quantification of CXCL10 was performed using an ELISA‐based assay on stored plasma at six months post‐transplant and pre‐treatment. Comparison was made with liver biopsies performed at 12 months and in the post‐transplant period where available. Results One hundred and thirty‐three patients were included. CXCL10 levels were lower in the slow fibrosis group compared to the rapid fibrosis group (p < 0.0001). CXCL10 correlated with F stage, necro‐inflammatory score, and serum transaminases (<0.0001). CXCL10 was an independent predictor of F ≥ 2 at 12 months and F ≥ 4 (p < 0.05). Pre‐treatment CXCL10 levels were an independent predictor of sustained virologic response (p = 0.04). Conclusions CXCL10 levels help identify patients with rapid fibrosis progression in patients with recurrent HCV and those that are likely to respond to AVT.